HUBUNGAN KONDISI RUMAH DENGAN KEJADIAN TUBERKULOSIS PARU - Yermi Yermi; Aisyah Ariffathul Ulum; Erni Kadir (Pascasarjana Universitas Negeri Makassar, 2022)
Dense housing conditions make it possible to spread germs from one human to another. Pulmonary tuberculosis is an infectious disease caused by Mycobacterium tuberculosis. Mycobacterial is transmitted through droplets in the air a person with pulmonary tuberculosis is the cause of pulmonary tuberculosis infection in the population. This study aims to determine the relationship between occupant density and ventilation conditions of the house with the incidence of pulmonary tuberculosis in Maros South Sulawesi. The type of research used is quantitative research with a descriptive survey design. The total sample of 33 home patients with positive pulmonary tuberculosis was determined by purposive sampling. The results showed a correlation between the occupant density of residents and home ventilation conditions with the incidence of pulmonary tuberculosis. Advice for family and community housing should have enough space especially for people with pulmonary tuberculosis that room made specifically to reduce the risk of transmission to residents sharing. House window to be created and placed in a way that ensures the sunlight can get into the main house in the morning because the sun can be deadly Mycobacterium tuberculosis.